2013
DOI: 10.1021/la304778d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curcumin on the Diffusion Kinetics of a Hemicyanine Dye, LDS-698, across a Lipid Bilayer Probed by Second Harmonic Spectroscopy

Abstract: The diffusion kinetics of a hemicyanine dye, LDS-698, across model membrane bilayers was studied in real time by the surface specific second harmonic technique. Using liposomes made from different headgroups, it has been established that the diffusion is initiated by electrostatic adsorption of the positively charged dye to the outer surface of negatively charged liposomes and its time constant is affected by the rigidity of the bilayer. In the presence of the liphophilic drug curcumin (curcumin/lipid mole rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 43 publications
6
32
0
Order By: Relevance
“…Therefore by monitoring the time dependent SH signal, which is proportional to the population difference of the ions adsorbed between the outer and inner surface the ionic transport process can be monitored in real time. The capability of this technique has first been demonstrated using an organic cation Malachite Green and later an organic anion Chlorin‐p6 and an organic cation LDS + . In this study we have used the LDS + ion to monitor its transport kinetics across the POPG bilayer in presence of the bile acids.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Therefore by monitoring the time dependent SH signal, which is proportional to the population difference of the ions adsorbed between the outer and inner surface the ionic transport process can be monitored in real time. The capability of this technique has first been demonstrated using an organic cation Malachite Green and later an organic anion Chlorin‐p6 and an organic cation LDS + . In this study we have used the LDS + ion to monitor its transport kinetics across the POPG bilayer in presence of the bile acids.…”
Section: Introductionsupporting
confidence: 70%
“…The instantaneous increase (< 1 second) in the E 2ω signal after addition of LDS + ions at 50 second time point is due to the rapid electrostatic adsorption of the positively charged dye on the negative charged outer bilayer surface of POPG liposomes. From here on, the E 2ω signal is dominated by contribution coming from the LDS + ions as demonstrated earlier . The E 2ω signal of LDS + ions decreases thereafter due to the transport of the LDS + from the outer to inner POPG lipid bilayer.…”
Section: Resultsmentioning
confidence: 99%
“…This could be related to the presence of the polyphenol between the carbon chains in the lamellar structure leading to an increase of the repetition distance. This increase (2.3 Å for the 3L structure) did not correspond to the curcumin size (close to 16 Å long and 4–5 Å wide) but the repetition distances determined by XRD corresponded to an average of the lipid structure. A lower shift toward lower angles was also reported for the double chain length structure.…”
Section: Resultsmentioning
confidence: 84%
“…It was expected that the rate of transport across the CM shouldb es imilar to those obtained from prior liposome-based studies. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In both cases, the molecular probe has to directly diffusea cross the lipid bilayer.S till, the deduced average moleculart ransport rate for the bacterial CM is found to be an order of magnitude slower compared to unilamellar liposomes (ca. 10 À3 s À1 )w hose lipid composition was homogeneous.…”
Section: A Mg Adsorption and Transport Through Individual Membranes mentioning
confidence: 99%
“…Following this demonstration,anumber of studies have since examined the effects of lipid composition and av ariety of environmental factorso nt he propensity and characteristics of molecular transport across membranes in model liposome systems. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The studies on liposomes suggested the feasibility that SHS could be used for monitoring molecular transport across membranesi nl iving biological cells. Indeed, in 2010, our laboratory reportedt he first demonstration that SHS could be applied to study molecular transport across membranes in living cells.…”
Section: Introductionmentioning
confidence: 99%